HOTS Oriented Problem-Based Learning Model: Improving Critical Thinking Skills and Learning Outcomes of Fifth Grade Students in Science Learning - Cantona, I Gede Eric; Suastra, I Wayan; Ardana , I Made (Thinking Skills and Creativity Journal, 2023)
The lack of application of learning models that provide HOTs problems causes low science learning outcomes and students' critical thinking skills. So that it is necessary to apply a model that can improve science learning outcomes and students' critical thinking skills, one of which is using a HOTs-oriented problem-based learning model. This study aims to analyze the effect of the HOTS-oriented problem-based learning model on students' critical thinking skills and science learning outcomes. The population of this study was all 150 students of fifth-grade Elementary School. The research sample was determined by random sampling technique with 75 students. The data needed in this study were collected through tests of critical thinking skills and learning achievement tests. After the data was collected, it was analyzed using MANOVA. The results of this study indicate: that there is a simultaneous effect of critical thinking skills and science learning outcomes between the groups taught by the HOTS-oriented problem-based learning model (F = 11.125 ≥ p = 0.05); there is a significant difference in students' critical thinking skills between groups of students who are taught with the HOTS problem-oriented problem-based model (F = 21.901 ≥ p = 0.05); and there is a significant difference in science learning outcomes between those who are taught with the HOTS problem-oriented problem-based model (F = 10.827 ≥ p = 0.05). Increasing students' critical thinking skills requires training students to solve a problem. Students are required to participate actively in asking and responding to questions so that students can develop their critical thinking skills.